Backflow-assisted time-resolved phase modulation in nematic liquid crystal Pi-Cells - Jin, Y; Elston, SJ; Fells, JAJ; Chen, B; Li, M; Kamal, W; Zhao, Z; Morris, SM (Elsevier, 2022)
By monitoring the time-dependent phase modulation behavior, we demonstrate the benefits of backflow on the phase modulation depth of nematic liquid crystal (LC) pi-cells in comparison to the phase modulation observed for other nematic LC device configurations. Specifically, results are presented for the time-resolved phase modulation of three different nematic LC device configurations under a range of electric field conditions: pi-cell (parallel-rubbed alignment layers), Fréedericksz cell (anti-parallel rubbed alignment layers), and a hybrid aligned nematic (HAN) device. The time-dependent behavior is obtained experimentally with a Michelson interferometer with a piezoelectric scanning mirror in the reference arm, which provides a continuous phase ramp in the reference signal. By recording the interference signal intensity, it is then possible to extract the change in optical phase as a function of time. It is shown that both the pi-cell and Fréedericksz cell exhibit a modulation that is greater than π radians for a double-pass configuration (2π radians for a four-pass configuration), with the lowest voltage amplitude corresponding to π phase modulation being observed for the pi-cell. Through the time-resolved response, it is shown that the presence of backflow hinders the dynamic phase response of the Fréedericksz device but does not negatively impact the behavior of the pi-cell. These results are found to be in good agreement with simulations of the phase modulation for the three nematic devices when backflow is taken into consideration.